Application of IAP-based Remote Updating Design to on Board Passenger Information Displays - 李卫红; 张凌云; 陈天喜; 李伦; 刘东亮 (机车电传动)
In order to solve the shortcoming of the on board passenger information, an IAP-based remote updating method was proposed, principle and running processes of which were introduced. This method could solve the problem of traditional method such as not flexible update and large amount of demolition work.